A new species of darkling beetles of the genus Blaps Fabricius, 1775 (Coleoptera: Tenebrionidae) from Turkmenistan and Iran - I.A. Chigray (Russian Academy of Science. Southern Scientific Centre. Federal Research Centre, 2020)
A new species of darkling beetles, Blaps ernesti sp. n., is described from the Southeast Caspian region (Turkmenistan, Iran). Allard was the first to describe this species in 1882, but he misidentified it as “Blaps variolaris Gemminger, 1870”, the junior synonym of Blaps rugosa Gebler, 1825, which is distributed in Russian Eastern Siberia, China and Mongolia. Seidlitz in 1893 and subsequent authors interpreted the Irano-Turkmen species as Blaps variolaris with the authorship of Allard, which is contrary to Article 49 of the International Code of Zoological Nomenclature. The new species is morphologically similar to Blaps mortisaga Linnaeus, 1758 but differs in the very coarse and dense punctation of its pronotum and elytra, in contrast to fine and sparse pronotal punctation and smooth elytra in the latter species. The basal duct of the spermatheca, between the vagina and reservoirs of the spermatheca of B. mortisaga, is short relative to the long accessory gland, reservoirs of the spermatheca are thin and elongated, the 1st reservoir is widened at the apex and 1.5 times longer than the 2nd reservoir. The basal duct of the spermatheca in Blaps ernesti sp. n. is very long relative to the short accessory gland, reservoirs of spermatheca are fusiform in the apical half, the 1st reservoir is slightly longer than the 2nd one. The new species is externally similar to Blaps dehaani Baudi di Selve, 1875 by punctation of pronotum and elytra, but differs in the larger body (18–28 mm vs 15–20 mm), very long male mucro and the hair tuft between abdominal ventrites 1 and 2